EFEKTIVITAS BAHASA ARAB DALAM MENULIS KARANGAN DI MA UMMUL QURO AL-ISLAMI - Roilah; Lukman Taufik Akasiah Tia (Al-Mubin, 2018)
This study aims to determine the effectiveness of learning Arabic in writing essays at MA Ummul Quro Al-Islami. Writing skills are one of the languages that are important in learning Arabic. The method used is a qualitative method, which is a research method that uses analysis, the research subjects in this study amounted to 20 students. The instrument used in this study was a test. And it can be concluded that the skill of writing descriptive essays (insya) is less effective, as evidenced by only a few students who can write essays (insya) correctly, and the other students are less effective in writing essays